Mainstreaming nature-based solutions in Dar es Salaam, Tanzania: a capacity perspective on transformative change - Ernita van Wyk; Luke Moore; Emma Lecavalier; Augustin Berghöfer; Raphael Karutz; Alphonce Kyessi; Gillian Maree (Nature-Based Solutions)
The potential of nature-based solutions (NBS) to support transformative change is gaining wide attention. NBS are attractive to policy- and decision-makers because they can generate biodiversity gains, alleviate poverty, mitigate climate change impacts, promote local economic opportunities, offset biodiversity loss and advance efforts towards social justice. This paper considers a set of urban NBS mainstreaming tools for the City of Dar es Salaam, Tanzania, developed within the context of a grant-funded project. The development and ‘performance’ of these tools are analysed, in terms of their potential to support transformative capacity. This qualitative practice review shows that the NBS tools supported transformative capacity development components such as effective engagement of intermediaries and co-production of knowledge. Multiple entry points for transformative capacity and opportunities for iterative reflection and action are ideal for supporting transformative capacities during the course of a typical project. However, a deliberate approach to capacity enhancement is necessary to achieve more targeted outcomes for urban transformation by applying NBS tools. Without purposefully planning for capacity enhancement, positive outcomes may be present but fortuitous, undermining the potential for NBS mainstreaming to lay foundations for transformative change. This critical review of NBS practice suggests that purposeful incorporation of transformative capacity into project design and practice, including enabling conditions for practitioners and funders, is key to directing transformation through NBS.